2019
DOI: 10.1111/wre.12376
|View full text |Cite
|
Sign up to set email alerts
|

Multiple resistance of Papaver rhoeas L. to 2,4‐D and acetolactate synthase inhibitors in four European countries

Abstract: SummaryThe issue of cross‐ or multiple resistance to acetolactate synthase (ALS) inhibitors and the auxinic herbicide 2,4‐D was investigated in Papaver rhoeas L., a common and troublesome weed in winter cereals, in a broad‐scale study across four European countries. A combination of herbicide sensitivity bioassays and molecular assays targeting mutations involved in resistance was conducted on 27 populations of P. rhoeas originating from Greece (9), Italy (5), France (10) and Spain (3). Plants resistant to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Both corn poppy and cornflower are insect pollinated. However, corn poppy is highly self-compatible; it exhibits significant genetic variation and a high phenotypic plasticity, which cause variable coloration of the crown petals and variable leaf shapes [49,50]. Genetic diversity in corn poppy populations indicates its high potential for adaptation to changing environmental conditions and its ability to settle new habitats [51,52].…”
Section: Biology and Distribution Of Corn Poppy And Cornflowermentioning
confidence: 99%
See 3 more Smart Citations
“…Both corn poppy and cornflower are insect pollinated. However, corn poppy is highly self-compatible; it exhibits significant genetic variation and a high phenotypic plasticity, which cause variable coloration of the crown petals and variable leaf shapes [49,50]. Genetic diversity in corn poppy populations indicates its high potential for adaptation to changing environmental conditions and its ability to settle new habitats [51,52].…”
Section: Biology and Distribution Of Corn Poppy And Cornflowermentioning
confidence: 99%
“…2,4-D is one of the most widely used herbicides and has been available on the market since 1945 [82]. Significant also is a selection of corn poppy biotypes with multiple resistance to different herbicides of the sulfonylurea group and also 2,4-D or MCPA [11,50,83]. Kotoula-Syka et al [84] identified a poppy biotype from Bafra (north Greece) that was highly resistant to chlorsulfuron, but also cross-resistant to tribenuron, triasulfuron, thifensulfuron and imazethapyr.…”
Section: Characteristics Of Herbicide-resistant Corn Poppymentioning
confidence: 99%
See 2 more Smart Citations
“…It is expected that the number of cases will increase trough the next years due to both new uses of 2,4-D enabled by the introduction of 2,4-D R crops, and also its incremental use due to greater dependence on SAH in response to the emergence of resistance to other herbicides [23]. Among many countries, very important new weeds R to 2,4-D have been cited: Amaranthus hybridus from Argentina [24] and Parthenium hysterophorus from Cuba [25], in which enhanced metabolism seems to be involved, and Papaver rhoeas is now spreading in France and Italy [26]. Other cases have been reported but not yet investigated, including Conyza canadensis from Hungary and C. sumatrensis from France, both found in vineyards, and Hirschfeldia incana from Argentina in winter cereals, reported by the co-author Dr. Vigna [11].…”
Section: Introductionmentioning
confidence: 99%